IMPLEMENTASI KEBIJAKAN RUANG TERBUKA HIJAU DI KOTA TARAKAN - Hastuti, Hastuti; Madani, Muhlis; Mustari, Nuryanti (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
The purpose of this research is to know the implementation of green open space policy in Tarakan city and to know the factors that influence the implementation of green open space policy in Tarakan city. The number of informants in this study was 7 people. This research used qualitative research method with phenomenology type. Technique of data collecting was used an instrument in the form of interview, observation an documentation. The results of this study indicated that the implementation of green open space policy in Tarakan city is not in accordance with the regulation that is only reached 18% yet. In addition, the existing green open space conditions are less well maintained. As for the supporting factors in this research is 1) Organizational behavior and interorganizational, 2) Lower-level bureaucratic behavior. While the inhibiting factor in this research is the behavior of the target group.